Klasifikasi Emosi Tokoh Utama dalam Novel Hai, Luka Karya Mezty Mez: Kajian Psikologi Sastra - Mulatsari, Annisa Harum; Onok Yayang Pamungkas (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2023)
This research aims to conduct a literary psychological study of the novel entitled Hai, Luka by Mezty Mez. This novel was written by a famous author who describes the complexity of the emotions and psychological conditions of the main character. This research explores the psychological elements contained in the novel and analyzes their influence on the character development of the main character. The method used in this research is qualitative method. The results of the research show that the classification of emotions in Dante's character is in the form of guilt, buried guilt, self-punishment, shame, sadness, hatred and love. In this case, the novel Hai, Luka provides a deeper understanding of the complexity of the characters and psychological conditions depicted through literary works. This research contributes to the field of literary psychology studies by revealing how authors use psychological elements to shape characters and stimulate emotional responses in readers